نمذجة تقلبات أسعار نفط البرنت خلال فترة جائحة Covid-19 "من 02/12/2019 إلى 26/01/2022" باستخدام نماذج Arch - بوخاري بولرباح (جامعة الوادي University of Eloued, 2023)
This study aimed to try to model the fluctuations of the daily series of Brent oil prices, using autoregressive models conditioned by the instability of the variance, during the period of the covid19 pandemic, specifically from 12/12/2019 to 26/01/2022, which is considered one of the Most of the periods that witnessed a significant change in Brent oil prices, due to the force majeure conditions witnessed by the oil market.
Modeling fluctuations in Brent oil prices during the Covid-19 pandemic period "from 02/12/2019 to 01/26/2022" using ARCH models.
Keywords: أسعار نفط برنت; سلاسل زمنية; نماذج الانحدار الذاتي المشروطة بعدم ثبات التباين; تقلبات